Pengaruh Model Pembelajaran Terhadap Peningkatan Prestasi Belajar Siswa Pada Mata Pelajaran IPS Terpadu Di SMA N 1 Sunggal - Riris Hotma Roito Manalu; Kristin Margaretha Simarmata; Sheryl Valencia Pangaribuan; Fitri Novi Yanti Munthe; Andi Taufiq Umar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is a type of descriptive qualitative research. The research method used to research on natural object conditions where the researcher is the key instrument. Therefore, this research was conducted qualitatively which aims to describe in detail and in depth about the Effect of Learning Model on Students' Learning Achievement. The case study design was chosen because the research focus on one school, namely SMAN 1 SUNGGAL, made it possible to analyze the specific and complex context of the use of learning models in integrated social studies subjects at the school. The subject of this study has been selected and determined by the researcher is the integrated social studies teacher at SMAN 1 Sunggal, specifically Dra. Marni Tarigan. Direct interviews were conducted with respondents at the school location on May 22, 2024, Data were collected through direct interviews using a structured interview guide. The interview was conducted once with the main respondent, Dra. Marni Tarigan. The results showed that the learning model is related to the level of student achievement, and the learning model will affect the final results and the ultimate goal of learning.